2021
DOI: 10.3389/fnut.2021.648893
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Neutralizes Hypothalamic Inflammation and Increases Weight Loss Without Altering Muscle Mass in Obese Rats Under Calorie Restriction: A Preliminary Investigation

Abstract: Obesity treatments, such as calorie restriction (CR), eventually lead to muscle wasting and higher rates of neuroinflammation, whereas hypothalamic inflammatory conditions impair body weight (BW) control. Nicotinamide riboside (NR) has been proposed against obesity but with little evidence on skeletal muscle tissue (SMT) and neuroinflammation. Therefore, we aimed to investigate the effects of CR on SMT and on hypothalamic inflammatory biomarkers in obese adult male Wistar rats, and whether NR supplementation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Benefits of NR supplementation have also been described in animal models of muscle disorders, such as models of mitochondrial myopathies [ 12 , 13 ] and of muscular dystrophy characterized by muscle wasting [ 14 , 15 ]. Furthermore, NR treatment improves muscle quality and physical performance in middle-aged mice [ 16 ] and preserves muscle mass during weight loss in obese rats under calorie restriction [ 17 ]. The positive outcomes of these and other pre-clinical studies are prompting human trials assaying the impact of NR supplementation on a variety of metabolic and exercise-related end-points in healthy adults, old persons, and persons with obesity, with disparate results so far [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of NR supplementation have also been described in animal models of muscle disorders, such as models of mitochondrial myopathies [ 12 , 13 ] and of muscular dystrophy characterized by muscle wasting [ 14 , 15 ]. Furthermore, NR treatment improves muscle quality and physical performance in middle-aged mice [ 16 ] and preserves muscle mass during weight loss in obese rats under calorie restriction [ 17 ]. The positive outcomes of these and other pre-clinical studies are prompting human trials assaying the impact of NR supplementation on a variety of metabolic and exercise-related end-points in healthy adults, old persons, and persons with obesity, with disparate results so far [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results were unsurprising because most previous studies reported no changes in these variables [ 26 , 40 , 41 ]. In cases where ω-3 PUFA supplementation modified anthropometric parameters, the treatment administration period was longer than six months or was complemented with physical activity, dietary, and pharmacological therapy [ 25 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deep muscular plane of the leg was identified, and the soleus skeletal muscle was dissected (following the natural lines), separating it from the underlying tendons to determine absolute weight. Subsequently, the relative weight was calculated with the absolute weight of the soleus muscle (g)/Body weight (g) × 100 [ 25 ]. Finally, the soleus skeletal muscle was stored at −30 °C with QIAzol lysis reagent for later processing.…”
Section: Methodsmentioning
confidence: 99%
“…NRS provided daily to suckling male mice improved lipid and energy metabolism in skeletal muscle and liver in adulthood, correlated with an upregulation of SIRT1 and AMP-dependent protein kinase signaling pathways [ 153 ]. In obese rats under CR, NRS (400 mg/kg for four weeks) neutralized hypothalamic inflammation by reverting high levels of TNF-α and increases weight loss without altering skeletal muscle mass [ 154 ]. Further, high doses (9 g/kg diet) of NRS for 18 weeks induced glucose intolerance and WAT dysfunction in male C57BL/6JRccHsd mice fed a mildly obesogenic diet (MOD) containing low but adequate tryptophan [ 155 , 156 , 157 ].…”
Section: Nicotinamide Riboside As a Tool To Mitigate Metabolic Disordersmentioning
confidence: 99%